PERANAN DESA MOJO DALAM PENGEMBANGAN DESA WISATA DI KECAMATAN KALITIDU KABUPATEN BOJONEGORO - Lia Wasilatul Azizah; Latifah Anom; Hafidza Nash'ul Amrina (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2018)
This research was conducted in Desa Mojo Kecamatan Kalitidu Kabupaten Bojonegoro. The purposes of this research are first, to describe the potential of Desa Mojo as a tourism village, second, to describe the role of desa Mojo in developing tourism in Kecamatan Kalitidu. Third, to describe the eagerness of the entrepreneur and the citizen in developing desa Mojo as a tourism village. The method of this research is descriptive qualitative. The data was taken by unstructured interview to the headman of Desa Mojo, the secretary of headman, and the entrepreneur. The result of the research are (1) Desa Mojo has a high tourism potential such as star fruits farm, bananas farm, Mojo Bahari tourism, and pleasurable place for tourism. (2) The role of Desa Mojo in developing tourism aspect through collaboration and partnership. (3) The eagerness of Desa Mojo citizen in developing tourism such as the expansion of the farms and building more gazebos for the vendors.